Some crack problems in composite materials with aerospace applications - Viswambharan Sreekanth (2015)
ABSTRACT Fiber reinforced composite materials have been widely used in various advanced engineering structures and devices, such as aircraft structures, tankers, ships, helicopters and building structures. A composite material is made of two or more different materials which could provide completely different properties from their constituents. During fabrication and application of composite materials, defects such as void, cracks may exist and cause damage. Fracture mechanics theory helps to identify and evaluate the initial defects and how they could lead to the material failure. Modern crack testing like NDT have several disadvantages. For example eddy current testing can be only carried if the probe could access the affected material region. Penetrant test only can detect surface cracking. Ultrasonic test results need interpretation, very thin section materials difficult to be tested. This project covers the parametric study of the stress intensity factor of crack in composite materials. A two dimensional benchmark model with a crack at the center was created and the stress intensity factor at the crack tip KI and KII were evaluated. The main purpose of the project was to analyze the relationship between changes in the stress intensity factor when the material property varied. The Abaqus 6.10 FEA software is used to model and evaluate the stress intensity factor at the crack tip in fiber reinforced composite materials. Two dimensional material analysis is conducted to model composite materials and stress intensity factors KI and KII at the crack tip were recorded using this software. The numerical simulation data show that the stress intensity factor decreases with the increasing elastic modulus ratio of the fiber and matrix, and increases when the modulus ratio is lower. Some real life applications are used to better describe the effect of fiber in a composite material and the difference in material strength compared to pure matrix material case.